Therapeutic Uses and Pharmacological Properties of Garlic, Shallot, and Their Biologically Active Compounds - Peyman Mikaili; Surush Maadirad; Milad Moloudizargari; Shahin Aghajanshakeri; Shadi Sarahroodi (Iranian Journal of Basic Medical Sciences, 2013)
Objective(s): Garlic (Allium sativum L. family Liliaceae) is well known in Iran and its leaves, flowers, and cloves have been used in traditional medicine for a long time. Research in recent decades has shown widespread pharmacological effects of A. sativum and its organosulfur compounds especially Allicin. Studies carried out on the chemical composition of the plant show that the most important constituents of this plant are organosulfur compounds such as allicin, diallyl disulphide, S-allylcysteine, and diallyl trisulfide. Allicin represents one of the most studied among these naturally occurring compounds. In addition to A. sativum, these compounds are also present in A. hirtifolium (shallot) and have been used to treat various diseases. This article reviews the pharmacological effects and traditional uses of A. sativum, A. hirtifolium, and their active constituents to show whether or not they can be further used as potential natural sources for the development of novel drugs.